Contribution à l’étude des systèmes des exploitations agricoles dans la région d’El Oued - DJERID, Boubekeur; LAHWEL, Abd Eldjalil; BENOUIDJEM, Ali; LAYEB, Saad (جامعة الوادي - University of Eloued, 2022)
As part of a study of the perimeters of agricultural development in the region of El oued, we have collected a set of elements of analysis which have enabled us to highlight the different most remarkable farming systems and to identify government programs and strategies and their influence on the types of farming systems that exist on the ground. The first elements of analysis first allowed us to differentiate between the different types of farming systems (large farms and those of small farms). As they allowed us to identify the farmer's strategy and their influence on the type of farming system. Secondly, we highlighted the adoption and adaptation of agricultural techniques introduced in the area and the main peasant innovations. This study also made it possible to highlight the main strategic objectives of farmers and the adaptations and readjustments in relation to the objectives of agricultural development
Production végétale
Keywords: farming system; farmer strategy; typology; production system; agricultural development; نظم المستثمرة الفلاحیة.إستراتجیة الفلاحین. نماذج المستصلحة. نضام الإنتاج الاستصلاح الزراعي